First record of Onthophagus (Furconthophagus) sellatus Klug, 1845 for Europe (Coleoptera Scarabaeidae: Onthophagini) - Daniel Patacchiola (PAGEPress Publications, 2021)
Onthophagus (Furconthophagus) sellatus Klug, 1845 (Coleoptera Scarabaeidae: Onthophagini) is recorded for the first time for Europe based on specimens collected in the south-western coastal area of Sicily (Siracusa province). This is a species with wide distribution encompassing the north-eastern portion of Northern Africa,Middle East and Arabian peninsula and a great portion of the Afrotropical region.